The relevance of lipid accumulation in lysosomal storage diseases in immune cells function - Ribeiro, Helena Maria Moreira Ferreira Soares (2020)
Lysosomal storage diseases (LSDs) are rare genetic diseases in which different molecules accumulate in the lysosome due to defects in lysosomal proteins. Fabry disease, Gaucher disease and Niemann-Pick disease type C (NPC) are LSDs, sphingolipidoses in which there is the accumulation of different sphingolipids in the lysosome while mucopolysaccharidoses (MPS) are characterized by the lysosomal accumulation of glycosaminoglycans. The lysosome is important in lipid antigen presentation mediated by CD1 molecules. In humans, four CD1 isoforms (CD1a, CD1b, CD1c and CD1d) are able to present lipid antigens, including sphingolipids, to a specific group of T cells, the CD1-restricted T cells. Invariant natural killer T (iNKT) cells are the most well characterized CD1-restricted T cells. In this thesis, it was investigated how the lysosomal alterations occurring in LSDs have an impact in the immune response, namely in CD1 lipid antigen presentation and in infection. CD1 lipid antigen presentation capacity was evaluated in monocytes and in monocyte-derived dendritic cells from LSD patients as well as the iNKT cell frequency. In Fabry, Gaucher, NPC and MPS VI diseases, monocyte-derived dendritic cells do not present defects in CD1b and CD1d lipid antigen presentation capacity and no alterations were found in iNKT cell frequency, contrarily to what was reported in several LSD mouse models. Also, in Fabry and Gaucher diseases, the monocyte CD1d lipid antigen presentation capacity was not decreased. In addition, the impact of different blood collection conditions in the CD1d lipid antigen presentation capacity of monocytes was investigated. Importantly, monocytes isolated 24 hours after blood collection in ethylenediamine tetraacetic acid (EDTA) presented a reduced capacity to activate iNKT cells, comparing to monocytes isolated 24 hours after blood collection in citrate. This finding is rather relevant in the field of CD1d lipid antigen presentation and highlights the importance of the anticoagulant chosen to perform monocyte functional assays. Macrophages are severely affected in Gaucher disease patients and human Gaucher disease macrophages presented an impaired capacity to fight bacterial infections. Herein, mouse Gaucher disease macrophages capacity of phagocytosing and eliminating Leishmania parasites was evaluated. It was used an in vitro model by treating mouse bone marrow-derived macrophages with an inhibitor of the enzyme β-glucocerebrosidase (Conduritol B epoxide), mimetizing the Gaucher disease. These Gaucher disease macrophages were able to internalize and kill the parasites, similarly to control cells. Altogether, these results contribute to increase the knowledge in LSDs and in CD1 lipid antigen presentation.